Indole Degradation in a Model System and in Poultry Manure by Acinetobacter spp. - Tujuba Ayele Tesso; Guohua Liu (Applied Sciences, 2019)
Indole degradation in a model system and in poultry manure was studied using an enrichment culture of two Acinetobacter species; Acinetobacter toweneri NTA1-2A and Acinetobacter guillouiae TAT1-6A. Degradation of indole was quantified using reverse phase high performance liquid chromatography (HPLC). The two strains were capable of degrading initial concentrations of indole ranging from 58.58–300 mg/L. The degradation efficiency was 66.36% (NTA1-2A), 94.87% (TAT1-6A), and 96.00% (mix) in 6 days when the initial concentration <300 mg/L. The strains were tested for enzymatic activity using 120 mg/L indole. The enzyme extracts of NTA1-2A and TAT1-6A from culture medium degraded indole completely, and no appreciable change of indole concentration was witnessed in the control group. The NTA1-2A, TAT1-6A, and the mix of strains were also used for in vivo poultry manure fermentation and removed 78.67%, 83.28%, and 83.70% of indole, respectively in 8 d. The strains showed a statistically significant difference (p < 0.05) in indole removal efficiency compared with the control, but no significant difference between the two strains and the mix in indole removal capacity. We concluded that A. toweneri NTA1-2A and A. guillouiae TAT1-6A are promising strains to remove indole and its derivatives to control the notorious odor in poultry and other livestock industries.